Концептуалізація духовних цінностей в українському науковому дискурсі й поетичному мовомисленні - Черненко, Ольга Ігорівна (My University, 2019)
The article deals with the conceptualization of the spiritual values. They have been considered through the prism of the evolution of values from the times of an ancient Chinese philosophical thought to the heyday of modern Ukrainian philosophical ideas. The existence of the values in the Ukrainian poetic space has been also researched. The emphasis has been placed on the linguistic aspects of creativity of artists, who distinguish the images of women among other valuable values in society. It has been determined, with the help of which language expressive means, a woman's image is differentiated in the works of V. Boyko and other masters of artistic word.
Conceptualization of moral values in Ukrainian scientific discourse and positive course
Keywords: психоемоційний стан людини; гармонія; теорія людиноцентризму; особистість; художній концепт; image; woman; philosophical thought; conceptualization; scientifi c discourse; language of thinking; poetry